2014
DOI: 10.1007/s00586-013-3109-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MRI signal changes in the adjacent pedicle of adolescent patients with fresh lumbar spondylolysis

Abstract: MRI revealed a higher prevalence of L3 or L4 spondylolysis than observed with CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 13 publications
4
24
0
Order By: Relevance
“…L5 is the most frequent lesion level for lumbar spondylolysis [10]. The union rate of L5 lesions is lower than that for other levels [11,12]. In the present study, we also found that the rate of lesion union at the level of L5 was signi cantly lower than that for other levels.…”
Section: Discussionsupporting
confidence: 65%
“…L5 is the most frequent lesion level for lumbar spondylolysis [10]. The union rate of L5 lesions is lower than that for other levels [11,12]. In the present study, we also found that the rate of lesion union at the level of L5 was signi cantly lower than that for other levels.…”
Section: Discussionsupporting
confidence: 65%
“…The use of radiographs improves the early diagnosis of lumbar spondylolysis. 9,11,12 In addition, differences in the ethnic groups of the subjects may have affected the results. 13 The prevalence of lumbar spondylolysis in the 3 age groups included in the current study showed that approximately half of elementary school and junior high school students and one third of high school students had a positive diagnosis, and all of those with spondylolysis had a history of athletic activity.…”
Section: Discussionmentioning
confidence: 99%
“…3 History of athletic activity and symptoms at the first consultation. a Two patients had no such history at the first consultation and b two patients had been diagnosed incidentally from abdominal plain X-rays that had been taken for investigation of an acute abdomen Eur Spine J can heal spontaneously or more easily with conservative treatment before the fracture of the pars interarticularis is complete [14]. Thus, there may be a distinct pathomechanism for spondylolysis at L5 and at other levels.…”
Section: Discussionmentioning
confidence: 99%